Attitudes about Paid Parental Leave in the United States. Issue 1 (2nd January 2022) - Li, Qi; Knoester, Chris; Petts, Richard J.
ABSTRACT: Paid parental leave offerings in the United States are relatively rare and unequal. Yet, little is known about public opinions about paid leave and the factors that distinguish adults' attitudes about them. With the use of data from the General Social Survey, we investigated attitudes about paid parental leave availability, preferred lengths of paid leave offerings, and government funding of leave in the United States. We found overwhelming support for paid parental leave availability, an average preference for four months of paid leave offerings, and common support for at least some government funding for leaves. Older and more politically conservative individuals were consistently less supportive of paid parental leave availability, longer lengths of leave, and government funding of leave. Women, supporters of dual-earner expectations, black individuals, and those who were not working in paid labor were typically more supportive of generous paid parental leave offerings. These findings suggest that there have been longstanding desires for more widespread and generous paid parental leave offerings in the United States but that this has not yet been sufficient to prompt widely applicable policy changes across the nation.